2022
DOI: 10.1590/fst.07522
|View full text |Cite
|
Sign up to set email alerts
|

A novel process to separate the eggshell membranes and eggshells via flash evaporation

Abstract: Eggshell membrane is a kind of cheap, abundant resources with great potential utilization value. A variety of active ingredients in it can be used as raw materials for medicine, light industry and other industries. At present, soluble protein, collagen, keratin, sialic acid, hyaluronic acid and antimicrobial protein have been successfully extracted from eggshell membrane and exploited in various fields. This study aimed to separate the eggshell membrane for fully exploiting the potential utilization value of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Results showed that the sample stored at room temperature (ES-RT) has a higher content of free amino groups, indicative of a higher degree of protein hydrolysis. On the other hand, as expected (Chi et al, 2022), the fresh sample (ES-F) has the lowest content of free amino groups (lower degree of hydrolysis). Upon comparing the hydrolysis levels of two samples from the same batch, ES-RT and frozen (ES-Fr), a signi cant increase in the free amino group content was observed in the sample stored at room temperature.…”
Section: Evaluation Of Es and Esm Quality Under Different Storage Con...supporting
confidence: 77%
“…Results showed that the sample stored at room temperature (ES-RT) has a higher content of free amino groups, indicative of a higher degree of protein hydrolysis. On the other hand, as expected (Chi et al, 2022), the fresh sample (ES-F) has the lowest content of free amino groups (lower degree of hydrolysis). Upon comparing the hydrolysis levels of two samples from the same batch, ES-RT and frozen (ES-Fr), a signi cant increase in the free amino group content was observed in the sample stored at room temperature.…”
Section: Evaluation Of Es and Esm Quality Under Different Storage Con...supporting
confidence: 77%
“…The rape threshed mixture is composed of rapeseed, pod shells, short stems and light impurities. The suspension velocity of rapeseed, pod shells, short stems and light impurities are 7.4-9.4 m/s, 2.4-3.2 m/s, 6.3-11.2 m/s, and 1.1-3.2 m/s, respectively [26] . There is a crossover interval between the suspension velocity of the short stem and rapeseed.…”
Section: Cyclone Separation Cleaning Devicementioning
confidence: 97%
“…A variety of separation methods have been developed for the large-scale industrialized purification of ESM from eggshell [ 80 ] ( Table 2 ). These include microwave-assisted membrane detachment [ 81 ], flash evaporation [ 82 ], and dissolved air flotation [ 83 ]. Microwave-assisted separation consists of a weakening of the physical bonds between membranes and the eggshell.…”
Section: Membrane Extractionmentioning
confidence: 99%
“…Flash evaporation uses a batch reactor that takes advantage of the effect of pressure changes of a saturated liquid to separate the membrane. Chi et al reported a separation rate of ~69% [ 82 ]. Lastly, dissolved air flotation separates the membrane from the shell according to its differential density by applying a water flow and mixed air.…”
Section: Membrane Extractionmentioning
confidence: 99%